Manfaat Musik Bagi Balita - Putri, Khairunnisa Risnandar; Siregar, Achmad Zulfikar (Jurnal Sosial Politik dan Hukum, 2024)
As we know that children under the age of 5 years are an important age for brain development and mindset cultivation, or it can also be called the Golden Age. If the person who plays the role of a person wants their child to become someone who is an expert in music in the future, then parents can develop musical skills at this age. What about children who have numbness in speech, can children who have speech limitations not be able to play music? No, music can be used as an alternative medium in communication. Music also has several benefits for toddlers. Can all types of music be used for education and sharpen intelligence? No, only some types of music can be used for education and sharpening intelligence, and some can even create dependence. Music that can be used for education and media to sharpen human intelligence is music that has a balance of 3 elements.